Morphological Changes of Sharp Bends in Response to Three Gorges Project Operation at Different Discharges - Wang, Hongyang; Yao, Shiming; Lu, Yongjun; Zuo, Liqin; Liu, Huaixiang; Zhao, Zhanchao (Frontiers in Earth Science, 2022)
Dam construction often changes downstream fluvial processes by reducing sediment supply. Taking Tiaoguan reach and Laijiapu reach of the lower Jingjiang Reach downstream of the Three Gorges Project as examples, three-dimensional flow velocity, sediment, and bed elevation were observed in the two bends for investigating the impact of flow structure and sediment transport of different discharges on sharp bend morphology. Results indicated that the flow structure and sediment transport process in curved channels depended upon the flow stages, which affected the patterns of erosion and deposition along the point bars and concave banks. Flow separation and development of secondary flow were depended on the shapes of point bars and flow depths nearby, and the strength of secondary flow increased with flow discharge. The high flow discharges, which had high sediment carrying capacity and stream power, provided the main driving force for erosion on upstream point bar, thus the type and duration of floods were crucial factors in the morphological evolution of meandering bends. The reduction of sediment supply should be responsible for erosion on the point bars, causing the flow to migrate toward the convex banks. In meandering rivers with reduced sediment supply, retreats (push inward) of inner (convex) banks dominated advances (pull inward) of outer (concave) banks. In addition, the formation and development of concave-bank bars might relate particularly to meander curvature. This study is expected to constitute a reference for bank protection and river management in meandering bends downstream of reservoirs.